Quantitative Estimation of Antigen-Specific Cells in Human Blood After Rhythmic Cold Effect - Babijchuk, V. G. (Problems of Cryobiology and Cryomedicine, 2009)
There was performed an immune phenotyping of blood lymphocytes in 50–60 year-old men blood, the content of specific groups was determined with expressing phenotypic markers using flow cytometer after rhythmic cold efects. Cells of adaptive immunity were shown to have the unique characteristics due to the single-functioned receptors, locating on their surface. Nine RCE sessions were established to significantly improve the immune system function, contribute to strengthening of organism’s adaptation to the effect of unfavourable factors.